#TITLE_ALTERNATIVE# - Amalinadhi Putra (NIM: 13613042), Cahya
Reducing weight and size of a jet engine could make a big saving for the airplane industry. This could be achieved by increasing the performance of jet-engine compressor. Total pressure ratio and adiabatic efficiency were two important parameters that decided the performance of compressor. But, there was a problem in the optimization process, which was as the total pressure ratio value increases, the value of efficiency decreases, vice versa. Hence, multi-objective optimization was needed to do the optimization of compressor performance that has opposite objective function. This thesis presented the study of multi-objective optimization of a transonic compressor, NASA Rotor 37, by deforming its blade to maximize two opposite-objectivefunction, which were total pressure ratio and efficiency, using NSGA-II assisted by surrogate model and multi-objective Expected Improvement (EI) methods to cut-off optimization timebudget. There were two optimization cases in which blades were parameterized by two and three variables. The optimization succeded to obtain several optimum solutions termed as pareto optima. Two of them were the total pressure ratio-optimum blade increasing the pressure ratio to 2.03% with 2.08% decrease in efficiency while the efficiency-optimum blade increasing the efficiency ratio to 1.39% but decrease the total pressure ratio about 2.84%. Furthermore, the optimized blades found in this study yield lower losses performance because of the movement of the separation line toward the downstream direction. Also, the optimized blade had 0.39% improvement on total pressure ratio and 0.14% improvement of efficiency.